2021
DOI: 10.1177/00197939211063863
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Time at Work Not Working

Abstract: Racial differences in effort at work, if they exist, can potentially explain race-based wage/earnings disparities in the labor market. The authors estimate specifications of time spent on non-work activities at work by Black and White males and females with data from the American Time Use Survey. Estimates reveal that trivially small differences occur between non-Hispanic Black and non-Hispanic White males in time spent not working while on the job that disappear entirely when correcting for non-response error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Research has consistently shown that race-based earnings disparities exist in labor markets with White workers earning more on average. Darity et al (2022) use ATUS data to show that Black and White workers spend statistically equal time at work on nonwork activities, so wage discrepancies cannot be explained by shirking. In this article, I find that MJHs work similar hours across race and ethnicity, so the experiences of working more than one job are not likely to explain race-based earning discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently shown that race-based earnings disparities exist in labor markets with White workers earning more on average. Darity et al (2022) use ATUS data to show that Black and White workers spend statistically equal time at work on nonwork activities, so wage discrepancies cannot be explained by shirking. In this article, I find that MJHs work similar hours across race and ethnicity, so the experiences of working more than one job are not likely to explain race-based earning discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Borah and Basu (2013) present an application of conditional and unconditional quantile that leads to different results. Darity Jr. et al (2021b) also use the unconditional quantile regression to analyse the heterogeneous causal effect of race on labor market outcomes. It is important to note both methods are based on continuous distributions.…”
Section: Methodology For the Causal Estimationmentioning
confidence: 99%
“…(2012) (which would have been our preferred estimation method), or unconditional quantile as in Darity Jr. et al (2021b). 5 Thus, we have formed four quantiles subgroups based on total annual earnings, three quantiles subgroups based on total annual hours worked, and twelve subgroups by crossing quantiles hours worked and annual earnings.…”
Section: Methodology For the Causal Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, whiteness propagates the meritocratic illusion that all people have equitable opportunities to succeed and achieve the American Dream if they exert sufficient individual effort (Efird & Lightfoot, 2020; Malat et al., 2018). Yet, decades of empirical evidence reveal that marginalized and minoritized populations (especially those at the intersections of multiple marginalized identities) disproportionately bear the burden of adverse social outcomes and relatively poor health (Bailey et al., 2017; Darity et al., 2022; Geronimus et al., 2020; Kwate & Meyer, 2010; Pearson, 2008; Viruell‐Fuentes et al., 2012; Williams et al., 2019), so much so that the Centers for Disease Control and Prevention (CDC) named racism a public health crisis (CDC, 2021b). However, novel research (which we detail below) suggests that there is variation in the ways that whiteness affects White Americans: whiteness benefits the most privileged, while simultaneously hurting less privileged White individuals and society at large.…”
Section: Introductionmentioning
confidence: 99%